Beta cells intrinsically sense and limit their secretory activity via mTORC1-RhoA signaling - Saar Krell; Amit Hamburg; Ofer Gover; Kfir Molakandov; Gil Leibowitz; Kfir Sharabi; Michael D. Walker; Aharon Helman (Cell Reports)
Summary: Precise regulation of insulin secretion by pancreatic β cells is essential to prevent excessive insulin release. Here, we show that the nutrient sensor mechanistic Target of Rapamycin Complex 1 (mTORC1) is rapidly activated by glucose in β cells via the insulin secretion machinery, positioning mTORC1 as a sensor of β cell activity. Acute pharmacological inhibition of mTORC1 during glucose stimulation enhances insulin release, suggesting that mTORC1 acts as an intrinsic feedback regulator that restrains insulin secretion. Phosphoproteomic profiling reveals that mTORC1 modulates the phosphorylation of proteins involved in actin remodeling and vesicle trafficking, with a prominent role in the RhoA-GTPase pathway. Mechanistically, mTORC1 promotes RhoA activation and F-actin polymerization, limiting vesicle movement and dampening the second phase of insulin secretion. These findings identify a glucose–mTORC1–RhoA signaling axis that forms an autonomous feedback loop to constrain insulin exocytosis, providing insight into how β cells prevent excessive insulin release and maintain metabolic balance.